2016
DOI: 10.1002/eap.1399
|View full text |Cite
|
Sign up to set email alerts
|

Do multiple fires interact to affect vegetation structure in temperate eucalypt forests?

Abstract: Fire plays an important role in structuring vegetation in fire-prone regions worldwide. Progress has been made towards documenting the effects of individual fire events and fire regimes on vegetation structure; less is known of how different fire history attributes (e.g., time since fire, fire frequency) interact to affect vegetation. Using the temperate eucalypt foothill forests of southeastern Australia as a case study system, we examine two hypotheses about such interactions: (1) post-fire vegetation succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 57 publications
(120 reference statements)
2
39
3
Order By: Relevance
“…Our finding that many aspects of the invisible mosaic influenced forest and woodland vegetation structure contrasts with the results of Haslem et al. (), who found the effects of long‐term fire history on vegetation structure of foothills Eucalyptus forests was limited compared with the effects of the most recent fire (severity, time since fire), and environmental variables (e.g., rainfall; Haslem et al. ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our finding that many aspects of the invisible mosaic influenced forest and woodland vegetation structure contrasts with the results of Haslem et al. (), who found the effects of long‐term fire history on vegetation structure of foothills Eucalyptus forests was limited compared with the effects of the most recent fire (severity, time since fire), and environmental variables (e.g., rainfall; Haslem et al. ).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, Haslem et al. (, mixed eucalypt forest) found that properties of a recent severe wildfire overrode most effects of previous fire history on vegetation structure. There is therefore a need to better understand the extent to which wildfire modifies the effects of the previous fire history on habitat structure, and hence, whether it is important for post‐wildfire management, and attempts to re‐instate variation in time‐since fire, to account for the established invisible mosaic.…”
Section: Introductionmentioning
confidence: 89%
“…); however, interactive effects of multiple fires, particularly under high‐severity conditions, remain largely unquantified (Haslem et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, different animal taxa often show variable—or even opposite—responses to time since fire (Barton et al., ; Driscoll & Henderson, ; Smith et al., ; Watson et al., ). Further, while time elapsed since the last fire in an environment is a strong predictor of species abundance in many instances (Haslem et al., ; Kelly et al., ), some species also respond to other aspects of the fire regime, such as the frequency of past fires (Lindenmayer et al., ; Lindenmayer, Blanchard, et al., ). Finally, the effects of fire on biota can vary markedly between locations with distinct vegetation, climate or topography (Nimmo et al., ).…”
Section: Introductionmentioning
confidence: 99%